Efficacy of pirfenidone for idiopathic pulmonary fibrosis: An Italian real life study. Issue 7 (July 2015) - Harari, S.; Caminati, A.; Albera, C.; Vancheri, C.; Poletti, V.; Pesci, A.; Luppi, F.; Saltini, C.; Agostini, C.; Bargagli, E.; Sebastiani, A.; Sanduzzi, A.; et al.
Summary: Background: In this retrospective Italian study, which involved all major national interstitial lung diseases centers, we evaluated the effect of pirfenidone on disease progression in patients with IPF. Methods: We retrospectively studied 128 patients diagnosed with mild, moderate or severe IPF, and the decline in lung function monitored during the one-year treatment with pirfenidone was compared with the decline measured during the one-year pre-treatment period. Results: At baseline (first pirfenidone prescription), the mean percentage forced vital capacity (FVC) was 75% (35–143%) of predicted, and the mean percentage diffuse lung capacity (DLCO) was 47% (17–120%) of predicted. Forty-eight patients (37.5%) had mild disease (GAP index stage I), 64 patients (50%) had moderate IPF (stage II), and 8 patients (6.3%) had severe disease (stage III). In the whole population, pirfenidone attenuated the decline in FVC (p = 0.065), but did not influence the decline in DLCO (p = 0.355) in comparison to the pre-treatment period. Stratification of patients into mild and severe disease groups based on %FVC level at baseline (>75% and ≤75%) revealed that attenuation of decline in FVC (p = 0.002) was more pronounced in second group of patients. Stratification of patients according to GAP index at baseline (stage I vs. II/III) also revealed that attenuation of decline in lung function was more pronounced in patients with more severe disease. Conclusions: In this national experience, pirfenidone reduced the rate of annual FVC decline (p = 0.065). Since pirfenidone provided significant treatment benefit for patients with moderate-severe disease, our results suggest that the drug may also be effective in patients with more advanced disease.